ISLAM : ILMIAH DAN DAKWAH (Perspektif Filsafat Ilmu) - Syefriyeni, Syefriyeni (JIA (Jurnal Ilmu Agama), 2016)
This study sought to reinforce differences, as well as to find forms or teleological principles between scientific of Islam and Islamic preaching mission. The research use integrative, descriptive and analytical approaches on the existing bibliographical sources. Thus, the authors dissect the difference and teleological principles between Islamic preaching mission and Islamic science by philosophical approach to the philosophy of science (ontology, epistemology, and axiology). The results of this study are; in principle teleological and also in general, basically Islamic sciences and mission of preaching are the same. In a general sense both together toward God that attempt to reach an understanding of God. The difference is in terms of each delivery method. Scientific, is the process of searching for an understanding of God, through the traces of nature. It reveals God through searching for meaning of nature, humans, and the environment. It is intended for people who have learning capacity. While religious preaching aims to anyone. And, preaching no need to use testing methods, instead it has a variety of delivery methods.